2007
DOI: 10.1007/s10336-006-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic parentage in the tawny owl (Strix aluco) reveals extra-pair paternity is low

Abstract: We have investigated genetic parentage in a Swiss population of tawny owls (Strix aluco). To this end, we performed genetic analysis for six polymorphic loci of 49 avian microsatellite loci tested for crossspecies amplification. We found one extra-pair young out of 137 (0.7%) nestlings in 37 families (2.7%). There was no intra-specific brood parasitism. Our results are in accordance with previous findings for other raptors and owls that genetic monogamy is the rule. Female tawny owls cannot raise offspring wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Several studies have found that breeder density and extra-pair paternity rate are positively correlated among populations of the same species (Møller and Ninni 1998), but they failed to determine if this relationship was causal or due to other covariate factors (Griffith et al 2002). Nonetheless, our results agree with those of other studies on socially monogamous species of raptors that revealed low to null rates of EPFs (Rudnick et al 2005;Saladin et al 2007). Our results suggest that Griffon Vultures are genetically monogamous.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Several studies have found that breeder density and extra-pair paternity rate are positively correlated among populations of the same species (Møller and Ninni 1998), but they failed to determine if this relationship was causal or due to other covariate factors (Griffith et al 2002). Nonetheless, our results agree with those of other studies on socially monogamous species of raptors that revealed low to null rates of EPFs (Rudnick et al 2005;Saladin et al 2007). Our results suggest that Griffon Vultures are genetically monogamous.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, high copulation rates are common in raptors (Mougeot et al 2002), and are supposed to be an effective behavior for ensuring male paternity, fidelity and investment in chick rearing for the female (Hunter et al 1993;Birkhead and Møller 1998). Moreover, the high investment of each parent in chick rearing restrains them from seeking EPC (Saladin et al 2007). The low to null EPF rate observed here, which must be confirmed in larger populations, makes it possible to directly estimate the effective population size from a breeding pair census.…”
Section: Discussionmentioning
confidence: 65%
“…Also, almost all owls, including Strix species, have similar mating systems (i.e. monogamous, territorial, males do all resource provisioning in early reproductive stage) and show low rates (Saladin et al 2007) or no evidence (Marks et al 1999, Arsenault et al 2002, Koopman et al 2007) of extrapair paternity. Even high frequencies of extrapair copulations may not actually lead to extrapair fertilization events in owls (Hsu et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We marked chicks with nontoxic color paint before they were old enough to be banded with an aluminum-numbered band. Extra-pair paternity is rare in the barn owl ), tawny owl (Saladin et al 2007), and swifts (Martins et al 2002). Eggs hatch every 2.5 days in the barn owl, 3.5 days in the tawny owl, and 1 day in the Alpine swift, thereby creating a pronounced age hierarchy among nest-mates.…”
Section: General Methods and Study Organismsmentioning
confidence: 99%